Are Chinese Happy (幸福)? : Evidence From the World Value Survey (2012) - Yang, Zhao; Li, Yan (My University, 2018)
Happiness, or life satisfaction, or well-being has become a hot and hotter topic in not only psychological study but also behavioral economics. In 2012, a national survey was conducted by asking Chinese respondents “are you happy?” during the Mid-Autumn Day and National Day in China. Since then, the issue of happiness has drawn wide public attention in China. Happiness is a critical factor to influence human behaviors, which will in turn affect the efficiency of the workplace or even the whole labor force. Therefore, our study on happiness is important and relevant. Most happiness studies so far have been done in developed countries, but this work just got started in China. The previous research on Chinese happiness tended to be qualitative. In this project, we use the empirical evidence to do a quantitative investigation about Chinese well-being.
Color poster with text and charts.
Keywords: National characteristics, Chinese; Happiness; Posters